Stakeholders’ Attitude on The Willingness-To-Pay Value For The Conservation Of The George Town, Penang World Heritage Site - Mohd Ariffin, *Noor Fazamimah; Ahmad, Yahaya; Alias, Anuar (Journal of Surveying, Construction and Property, 2015)
The objective of this research is to test the significant relationship between the attitudes and responses of the stakeholders, and the willingness-to-pay (WTP) for the conservation of the George Town Penang World Heritage Site (GTWHS). This research applied a contingent valuation survey questionnaire in collecting the data. A total of 300 local residents and 150 tourists were randomly interviewed in the George Town Conservation Zone area. From the study, there was a positive relationship between the principal stakeholders’ attitude towards the UNESCO WHS status, the importance of preserving the non-use value and the conservation management of the GTWHS. It was proves that there was an awareness among the stakeholders towards conserving their cultural heritage. This research study has found that the stakeholders’ attitude towards the WHS status, cultural tourism and the important of preserving the non-use value as a local resource is vital in establishing a sustainable conservation management of the GTWHS. This could give a fair view of the attitude of the interest groups with a stake towards the cultural heritage and development, common level of cultural understanding and consciousness of the community. Analyzing values through a participatory process which have involved the various interest groups with a stake in a place or object could help promote the sustainability of the conservation efforts of the GTWHS.